Legal Regulation of Public Health Emergencies within the framework of the work and guidelines of the World Health Organization - Zangana, Esmael Najmadin; Gharib Mala, Shamal (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The framework of the study is an analytical reading of the work and recommendations of the World Health Organization (WHO) In the face of threats to public health, Especially in light of global health guidelines, which require measures to prevent the spread of disease internationally by declaring a health emergency In light of the means of implementing the recommendations and emphasizing the legal nature and obligations of member states, Iraq as a member of the organization has infiltrated this legal framework from the Public Health Law of 1981 reflecting the fact that the organization is committed to its obligations In light of the legal arrangements made by the Legislative Council.